Transcriptomic analysis and volatile profiling reveals the regulatory mechanism of flavor volatiles in fresh-cut potatoes - Liping Hong; Wenhui Zhang; Fei Chen; Enming He; Jingwen Wu; Wenhua Wang (International Journal of Food Properties, 2023)
ABSTRACTThe potato (Solanum tuberosum L.) is one of the most edible vegetables worldwide. The cutting process disrupts the internal structure of several volatile substances that prompt flavor changes in fresh-cut potatoes. Understanding the composition of volatiles along with their biosynthesis mechanism is important to preserve original potato flavor during processing technology. This study characterized the volatile profiles and gene expression of fresh cut potato shreds at 0 hour (CK) and after 4 hours of storage (CK4). According to volatile profiling, alkanes were found to be the most abundant volatiles, followed by alcohols, aldehydes, esters, furans, and quinone. The abundance level of these volatiles was reduced many folds in CK4 potato shreds except for specific alkenes such as hexane, 1,3-hexadiene, and 1,6-octadiene. The transcriptome analysis revealed 5961 differentially regulated genes. An array of differential genes had functional annotations with biological responses to wounding, alcohol, water deprivation, and the molecular activity of acetyltransferase. In addition, most of these genes had pathway enrichment into the biosynthesis of secondary metabolites, alpha-linolenic acid metabolism, fatty acid biosynthesis, degradation, elongation, and metabolism. In particular, the many-fold differential regulation of the hydroperoxide pathway encoding genes probably yielded different volatile profiles that cause flavor disorders even after storage of fresh cut potato shreds for a few hours. Our results determined major flavor volatiles in fresh cut potato and identified important genes associated with the regulation of flavor volatiles in potato shreds. Our results will facilitate development of optimal management practices for preserving fresh-cut potatoes quality.